Main controlling factors of natural fractures in tight reservoirs of the lucaogou formation in the jimsar sag, Xinjiang, China - Yu, Yixin; Deng, Ze; Gao, Jinliang; Li, Peng; Zhang, Chen (Frontiers in Earth Science, 2023)
Natural fractures act as critical flow channels and reservoir space in the Lucaogou Formation tight reservoir of the Jimsar Sag. It is essential to identify the main controlling factors of natural fractures in order to achieve efficient development of tight oil in this area. There are mainly three types of natural fractures, including tectonic fractures, diagenetic fractures, and abnormal overpressure-induced fractures. Diagenetic fractures are predominantly bedding seams. The fracture development is affected by multiple factors including brittle minerals, lithology, tectonic stress, bed thickness, and total organic carbon (TOC). Large tectonic stress, smaller bed thickness, and higher total organic carbon are all favorable for the development of tectonic fractures and bedding seams. The controls of brittle minerals and lithology on fracture development are different for tectonic fractures and bedding seams. Specifically, carbonate minerals stimulate the tectonic fracture development, while brittle minerals have no control over the bedding seam development; tectonic fractures are most developed in the dolomitic rocks, while bedding seams are most developed in the argillaceous rocks. The calculated fracture density variation coefficients reveal that tectonic stress and brittle minerals are the main controlling factors of tectonic fracture development; total organic carbon and lithology are the main control factors of bedding seam development.